2021
DOI: 10.3102/0034654321998072
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education of Students With General Learning Difficulties: A Meta-Analysis

Abstract: This article presents a meta-analysis on cognitive (e.g., academic performance) and psychosocial outcomes (e.g., self-concept, well-being) among students with general learning difficulties and their peers without learning difficulties in inclusive versus segregated educational settings. In total, we meta-analyzed k = 40 studies with 428 effect sizes and a total sample of N = 11,987 students. We found a significant small to medium positive effect for cognitive outcomes of students with general learning difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 93 publications
2
20
0
10
Order By: Relevance
“…Importantly, it agrees with the results from a meta-analysis of studies of mixed designs, which showed that typically developing students in European school systems do not benefit from learning in inclusive classrooms [ 3 ]. It is also in line with the results of the latest meta-analysis, which showed that according to longitudinal studies, the inclusion in classrooms of students with generalised difficulties in learning had no significant impact on the academic progress of their peers without such difficulties [ 70 ]. It is also important to notice that this meta-analysis showed a significant difference in the extent of the effect in longitudinal and cross-sectional studies–the latter showed a weak negative effect of inclusive education on the academic achievement of typically developing students [ 70 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Importantly, it agrees with the results from a meta-analysis of studies of mixed designs, which showed that typically developing students in European school systems do not benefit from learning in inclusive classrooms [ 3 ]. It is also in line with the results of the latest meta-analysis, which showed that according to longitudinal studies, the inclusion in classrooms of students with generalised difficulties in learning had no significant impact on the academic progress of their peers without such difficulties [ 70 ]. It is also important to notice that this meta-analysis showed a significant difference in the extent of the effect in longitudinal and cross-sectional studies–the latter showed a weak negative effect of inclusive education on the academic achievement of typically developing students [ 70 ].…”
Section: Discussionsupporting
confidence: 84%
“…It is also in line with the results of the latest meta-analysis, which showed that according to longitudinal studies, the inclusion in classrooms of students with generalised difficulties in learning had no significant impact on the academic progress of their peers without such difficulties [ 70 ]. It is also important to notice that this meta-analysis showed a significant difference in the extent of the effect in longitudinal and cross-sectional studies–the latter showed a weak negative effect of inclusive education on the academic achievement of typically developing students [ 70 ]. Although the relationship between study design and results is difficult to explain, it shows a need to conduct more longitudinal research, as it is more reliable for the assessment of the importance of inclusive education for the academic achievement of typically developing students.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Properly organised inclusion offers an optimal educational environment for the personality development of children, students with intellectual disabilities and members of the host community. Numerous research findings confirm the positive impact of inclusive education on cognitive (Krämer et al, 2021) and social development (Rafferty et al, 2003), the social competencies, and affective factors which support learning (De Bruin, 2020).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, students’ performances in specific curriculum-related domains could be assessed to check whether inclusive teaching approaches such as differentiated instruction, are successful considering outcome-oriented evaluation ( Deunk et al, 2018 ). The literature regarding SEN students’ academic achievements has shown that compared to when they are segregated into special classes or schools, they achieve better academic performances when they are allowed to integrate into regular classrooms ( Krämer et al, 2021 ). The academic performances of non-SEN students in inclusive classes are at the least similar to the academic outcomes of non-SEN students in regular classes ( Ruijs and Peetsma, 2009 ; Ruijs et al, 2010 ; Dessemontet and Bless, 2013 ; Dell’Anna et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%